EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KEMAMPUAN MENULIS TEKS PUISI PADA SISWA KELAS XI SMA NEGERI 19 MEDAN - Pratiwi, Nurul; Lubis, Fitriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the Cooperative Learning Model of the Group Investigation (GI) type on students’ ability to write poetry texts in grade XI of SMA Negeri 19 Medan. This study employed a quantitative approach with a quasi-experimental design using a Posttest-Only Control Group Design. The population consisted of 351 students, with 60 students selected as the sample through random sampling and divided into experimental and control groups. The instrument used was a poetry writing test assessed based on the physical and inner elements of poetry. The data were analyzed using statistical tests.The results showed that the mean score of the experimental group was 84.50, while the control group was 41.33. The hypothesis testing indicated that the significance value was 0.001 < 0.05, meaning that the alternative hypothesis (Ha) was accepted. Therefore, it can be concluded that the Group Investigation cooperative learning model is effective in improving students’ poetry writing skills.